Quality assurance in Asia-Pacific universities : implementing massification in higher education - Neubauer, Deane E.; Gomes, Catherine (International and development education, 2017)
This edited volume examines the importance of quality issues in contemporary higher education systems in the Asia Pacific. Part Three extends the research of higher education quality assurance in Hawaii Pacific University (HPU) and the diverse international student body in the Australian higher education system.